Correlating facet orientation, defect-level density and dipole layer formation at the surface of polycrystalline CuInSe2 thin films - Elizabeth, Amala; Conradi, Hauke; K. Sahoo, Sudhir; Kodalle, Tim; A. Kaufmann, Christian; Kühne, Thomas; Mirhosseini, Hossein; Abou-Ras, Daniel; Mönig, Harry (Acta Materialia)
Individual grains of chalcopyrite solar cell absorbers can facet in different crystallographic directions at their surfaces. To gain a deeper understanding of the junction formation in these devices, we correlate variations in the surface facet orientation with the defect electronic properties. We use a combined analytical approach based on scanning tunneling spectroscopy (STS), scanning electron microscopy, and electron back scatter diffraction (EBSD), where we perform these experiments on identical surface areas as small as 2 × 2 µm2 with a lateral resolution well below 50 nm. The topography of the absorber surfaces indicates two main morphological features: micro-faceted, long basalt-like columns and their short nano-faceted terminations. Our STS results reveal that the long columns exhibit spectral signatures typical for the presence of pronounced oxidation-induced surface dipoles in conjunction with an increased density of electronic defect levels. In contrast, the nano-faceted terminations of the basalt-like columns are largely passivated in terms of electronic defect levels within the band gap region. Corresponding crystallographic data based on EBSD experiments show that the surface of the basalt-like columns can be assigned to intrinsically polar facet orientations, while the passivated terminations are assigned to non-polar planes. Ab-initio calculations suggest that the polar surfaces are more prone to oxidation and resulting O-induced defects, in comparison to non-polar planes. Our results emphasize the correlation between morphology, surface facet orientations and surface electronic properties. Furthermore, this work aids in gaining a fundamental understanding of oxidation induced lateral inhomogeneities in view of the p-n junction formation in chalcopyrite thin-film solar cells.
Keywords: Chalcopyrite absorber; Scanning tunneling spectroscopy; Electron backscatter diffraction; Density functional theory; Surface dipole

Water structure near the surface of Weyl semimetals as catalysts in photocatalytic proton reduction - Gujt, Jure; Zimmer, Peter; Zysk, Frederik; Süß, Vicky; Felser, Claudia; Bauer, Matthias; Kühne, Thomas (Structural Dynamics)
Keywords: Spectroscopy; Condensed Matter Physics; Instrumentation; Radiation

Thin films of poly(vinylidene fluoride-co-hexafluoropropylene)-ionic liquid mixtures as amperometric gas sensing materials for oxygen and ammonia - Lee, Junqiao; Hussain, Ghulam; Lopez Salas, Nieves; MacFarlane, Douglas R.; Silvester, Debbie S. (The Analyst)
A gas sensor comprising of a planar electrode device covered with a thin layer of gel polymer electrolyte gave accurate and fast sensing responses for oxygen and ammonia detection in both the cathodic and anodic potential regions.
Keywords: Electrochemistry; Spectroscopy; Environmental Chemistry; Biochemistry; Analytical Chemistry

Controlling Self-Assembly with Light and Temperature - Carl, Nico; Müller, Wenke; Schweins, Ralf; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Self-Assembly of Fibrinogen in Aqueous, Thrombin-Free Solutions of Variable Ionic Strengths - Hämisch, Benjamin; Büngeler, Anne; Kielar, Charlotte; Keller, Adrian; Strube, Oliver; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Secondary Particle Formation during the Nonaqueous Synthesis of Metal Oxide Nanocrystals - Stolzenburg, Pierre; Hämisch, Benjamin; Richter, Sebastian; Huber, Klaus; Garnweitner, Georg (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

The Role of Electronic and Phononic Excitation in the Optical Response of Monolayer WS2 after Ultrafast Excitation - Ruppert, Claudia; Chernikov, Alexey; Hill, Heather M.; Rigosi, Albert F.; Heinz, Tony F. (Nano Letters)
Transient changes of the optical response of WS2 monolayers are studied by femtosecond broadband pump–probe spectroscopy. Time-dependent absorption spectra are analyzed by tracking the line width broadening, bleaching, and energy shift of the main exciton resonance as a function of time delay after the excitation. Two main sources for the pump-induced changes of the optical response are identified. Specifically, we find an interplay between modifications induced by many-body interactions from photoexcited carriers and by the subsequent transfer of the excitation to the phonon system followed by cooling of the material through the heat transfer to the substrate.
Keywords: Atomically thin 2D materials; carrier and phonon dynamics; ultrafast spectroscopy

Silica Polymerization from Supersaturated Dilute Aqueous Solutions in the Presence of Alkaline Earth Salts - Kley, M.; Kempter, A.; Boyko, V.; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Insight into the Final Step of the Supramolecular Buildup of Eumelanin - Büngeler, Anne; Hämisch, Benjamin; Huber, Klaus; Bremser, Wolfgang; Strube, Oliver I. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Joint Raman spectroscopy and HRXRD investigation of cubic gallium nitride layers grown on 3C-SiC - Rüsing, Michael; Wecker, T.; Berth, Gerhard; As, Donat Josef; Zrenner, Artur (physica status solidi (b))
Cubic gallium nitride (GaN) films are analyzed with highresolution X-ray diffraction (HRXRD) and Raman spectroscopy. Several cubic GaN layers were grown on 3C-SiC (001) substrate by radio-frequency plasma-assisted molecular beam epitaxy. The layer thickness of the cubic GaN was varied between 75 and 505 nm. The HRXRD analysis reveals a reduction of the full-width at half-maximum (FWHM) of omega scans for growing layer thicknesses, which is caused by a partial compensation of defects. The Raman characterization confirms well-formed c-GaN layers. A more detailed examination of the longitudinal optical mode hints at a correlation of the FWHM of the Raman mode with the dislocation density, which shows the possibility to determine dislocation densities by Ramanspectroscopy on a micrometer scale, which is not possible by HRXRD. Furthermore, this Raman analysis shows that normalized Raman spectra present an alternative way to determine layer thicknesses of thin GaN films.
Keywords: cubic gallium nitride; dislocation density; HRXRD; Raman spectroscopy